The Potential Availability Of Insects In The Vegetative and Generative Phase Of Wheat (Triticum Aestivum L.) In Bener Meriah District, Aceh Province - Muhammad Sayuthi; Lukman Hakim; Alfizar Alfizar; Marlina Marlina (The Faculty of Veterinary Medicine of Syiah Kuala University, 2020)
Abstract